Um estudo sobre a segmentação não-convencional na aquisição da escrita de alunos de EJA - Ferreira, Carmen Regina Gonçalves (2011)
The theme of this thesis deals with the non-conventional segmentation processes, hiposegmentations, hypersegmentations and hybrid forms which can be found in texts written by students who take part in EJA, a government project for the education of the youth and the adult. In this study, non-conventional segmentations of words are considered structures that arise from the hypotheses which the subjects have formulated in their writing acquisition process (FERREIRO & TEBEROSKY, 1999). This information is valuable linguistic material since it can give clues regarding the phonological knowledge these learners use when they write (ABAURRE, 1991). From this perspective, this study aimed at describing and analyzing the processes which adults go through - during their literacy process when they face the task of segmenting their writing according to conventions, as well as comparing these results to the ones related to child writing in order to check the adequacy of categories proposed by Cunha (2004) to the analysis of non-conventional segmentation in texts written by EJA students. The data used for analysis were extracted from texts written by three EJA students and collected longitudinally in text production workshops which aimed at creative and spontaneous texts. Results show that clitics, or forms that are similar to them, are mostly involved in non-conventional writing in data which refer to both hiposegmentations and hypersegmentations. Data provided by adults, as well as the ones got from children who were studied by Cunha (2004), reveal linguistic motivation which can be explained in the light of concepts related to the prosody of the language. The description and the analysis of such processes, identified at the beginning of adults writing processes, can lead to reflections that may help teachers with their pedagogical actions when teaching Portuguese to adults who are acquiring the written language